PENGOLAHAN IKAN BANDENG PRESTO MELALUI PEMBERDAYAAN MAJELIS TAKLIM DI DESA BORIKAMASE - Abna, Nurjannah; Syam, Netty (Jurnal BALIRESO, 2018)
are targeted to serve the people who live in Borikamase Village. The village of Borikamase is amilkfish producing village that is sold in fresh condition without processing to the local market orsent to other places in the vicinity. This potential needs to be developed into a business of milkfishpresto. The purpose of this activity is to provide skills: (1) read the Quran correctly, eloquently,and in accordance with the makhraj to the partner groups; (2) management of religious group(Majlis Taklim) systematically; (3) good presto fish processing method.The expected output targets of this activity are the literate and correct literacy skills of the Quran;the increasing management of the Majelis Taklim and the business establishment of a group ofPresto milkfish production. It is expected that partners can produce quality Presto fish products interms of product durability, taste, and packaged and hygienic, then partners become independent inthe business management of presto milkfish.